Implementação e repercussões fisiológicas da PEEP variável em ratos saudáveis - Jardim Neto, Alcendino Cândido (2017)
Mechanical ventilation with variable respiratory rate and/or tidal volume has been shown beneficial by promoting alveolar recruitment and decrease in cytokines expression. The use of protective low tidal volumes associated with a variable PEEP (Positive End-Expiratory Pressure) is a promising alternative strategy. Our objective was the development of a variable PEEP generator for small animals, based on the expiratory time control. The PEEP generator was evaluated by the assessment of individual PEEP transitions and the capacity to generate the desired PEEP frequency distribution. For evaluating the physiological effects, 24 healthy rats were sedated and paralyzed. Of these, 6 animals constituted the non-ventilated control group while the others were mechanical ventilated (VCV mode, RR: 70 ipm, Vt: 6 ml/kg, I:E: 1:2) and after recruitment maneuver (15 cmH2O) and PEEPEmin (PEEP of minimum elastance) titration, they were separated in three groups of 6 animals each and ventilated for 2 hours: Emin (invariable PEEP equal to PEEPEmin), G1c and G5c (PEEP of Gaussian distribution of mean equal to PEEPEmin and standard deviation of 1 cmH2O, with 1 and 5 ventilatory cycles per PEEP step, respectively). The controller as capable of generate PEEP with the desired frequency distribution. The analysis of in vivo data did not reveal significant differences among groups for ventilatory mechanics, gasometry, histology or biochemistry, with exception of interleukin -1β, different for the control group.